2013
DOI: 10.5772/56753
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Industrial Robot Programming for the Ceramic Industry

Abstract: This paper presents an interactive programming method for programming industrial robots in ceramic applications. The main purpose was to develop a simple but flexible programming system that empowers the user with product driven programming without compromising flexibility. To achieve this flexibility, a two step hybrid programming model was designed: first the user sketches the desired trajectory in a spatial augmented reality programming table using the final product and then relies on an advanced 3D graphic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…Ref. [14] presents an interactive programming method for using robots in the ceramic industry. This work aims to develop a robotic solution to finish ceramic tableware parts per the quality requirements.…”
Section: • Stereo Cameramentioning
confidence: 99%
See 1 more Smart Citation
“…Ref. [14] presents an interactive programming method for using robots in the ceramic industry. This work aims to develop a robotic solution to finish ceramic tableware parts per the quality requirements.…”
Section: • Stereo Cameramentioning
confidence: 99%
“…[15] describes a technique used for polishing/fettling ceramic pot handles using a robot system with a stepper motor, a ball screw, and a force sensor. As opposed to the previous example of the work presented in [14], the polishing tool is placed at the end of the robotic arm and is not an external system. The force actuation is controlled with a fuzzy PID (proportional integral derivative) controller instead of a regular PID to achieve a better response.…”
Section: • Stereo Cameramentioning
confidence: 99%
“…The previously refereed conditions force ceramic production companies to push the envelope toward the development of alternative manufacturing processes and the integration of cutting-edge technologies into the fabrication loop. For example, the use of virtual and augmented reality technologies [2], or machine vision for quality control [3] have been used to help achieve this goal. In addition, steps are being given toward a full industry digitalization, which will be able to interconnect the machines between the physical world and the virtual digital domain.…”
Section: Overviewmentioning
confidence: 99%
“…22,23 Virtual cues augmented in the real environment can support and enhance interaction between human and virtual robot at different stages of the task planning process. 24,25 In this work, a VR environment has been built to aid training of users in offline programming industrial robots. This does support full user immersion, but for the sake of simplicity of use and evaluation the first trials reported here concern its use in a third person non-immersive mode.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 Virtual cues augmented in the real environment can support and enhance interaction between human and virtual robot at different stages of the task planning process. 24,25…”
Section: Introductionmentioning
confidence: 99%